PALMS DIVERSITY, COMPOSITION, DENSITY AND ITS UTILIZATION IN THE GUNUNG HALIMUN SALAK NATIONAL PARK, WEST JAVA-INDONESIA WITH SPECIAL REFERENCE TO THE KASEPUHAN CIPTAGELAR - Wardah Wardah; JP Mogea (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Palms diversity, composition, and density in six selected sites of 15 rectangular plots of 100 x 20 m were successfully studied.The sites are in Kasepuhan Ciptagelar, which located in the Gunung Halimun Salak National Park in West Java.The sites are in the disturbed primary submontane forest at 800 to 1400 m altitude. Ethnobotanical observations made in some of the villages in Kasepuhan Ciptagelar proceeded through informal unending open interviews involving some traditional elders, prominent communities, and handicraftsmen. There is no species addition to the park from the Kasepuhan Cigelar. Three species of rattans(Calamus polysiachys, C. burcklanus, and Korthalsia laciniosa) are added to the park from Cibedug, Leuwijamang, Ciptarasa, and Cikidang. Young leaves of Daemonorops rubra are used for traditional Inner Baduy cloth. The use of C. javensis canes for bracelets and rings, and the infructescence of Plectocomia elongala for decoration are new findings.